DEVICES AS DIDACTICAL TOOLS FOR EXPERIMENTAL MEASUREMENTS - KVASNOVÁ, Petra (Trends in education, 2009)
The paper deals with the projection, implementation and use of devices for measuring surface properties of particular pollutant. These devices are using as didactical tools in the teaching process. Students measuring practical at these devices, execute the results and then the semester projects.
Keywords: angle of repose; glide slope angle; experimental device; didactical tools.